Aplicação de técnicas Lean no gerenciamento de produção: estudo de caso em uma obra na construção civil brasileira - Daniel Tarabal da Matta (2015)
Improving construction performance has been a challenge for practitioners, for its performance has been presenting worse results then the other industries. The term new production philosophy refers to a series of methods, tools and techniques originated in the Japanese JIT and TQC in the automobile industry, and it has been presenting good results. The possibility of the application of these techniques in construction has been developed since the work of Koskela, in 1992. This thesis is consisted, firstly, of a review of the literature on the theme, in order to give theoretical subsidy towards the implementation. Then, it is reported the analysis of a case study on the application of Lean concepts and techniques in the production management processes of a Brazilian construction site, in order to evaluate its gain potential and to point the main difficulties in the way. This thesis shows that, even in applications limited to the production management, i.e. to the construction site, it is possible to obtain good results and performance improvement. Another objective of this thesis is contributing to the knowledge of the field, which is in need of more application reports, especially in Brazil.